(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1912)
A pair of quern stones in splendid condition were found together in the roots of an oak tree which had been blown down during a recent gale. They are made of puddingstone and comprise the upper and lower stones of a rotary quern.